Rasch stacking analysis of student internet addiction based on gender - Yuda Syahputra; Prayitno Prayitno; Syahniar Syahniar; Hariyani Hariyani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
Education always experiences change and development under developments in all areas of life. Rapid technological developments make it easier for humans to carry out their daily activities. Technology that is experiencing rapid development is an information technology, one of which is the internet. This study aims to describe differences in internet addiction between male and female students at Universitas Negeri Padang. Sample of this study was 258 students (47 male and 211 female). The analysis technique used is independent of sample t-test combined with a stacking Rasch model. The results of analysis showed that there was no difference in internet addiction between male and female students at Universitas Negeri Padang. Internet addiction of male and female students has no difference, it can see from the ability of students to answer instrument statements are the same this is show by the value of internet addiction (sig =.233), this states p-value> 0.05, which shows there is no significant difference in internet addiction between male and female students. It further states the discussion regarding counseling and guidance services.